PENGEMBANGAN INDUSTRI PARIWISATA KEPULAUAN SERIBU MELALUI PENINGKATAN KUALITAS SUMBER DAYA MANUSIA (SDM) (Studi Pada Suku Dinas Pariwisata Dan Kebudayaan Kepulauan Seribu) - Pantriko Muhammad; Arik Prasetya (Jurnal Administrasi Bisnis, 2018)
This type of research is using exploratory research with the formulation of the problem, such as (1) how the active role in Tourism and Culture offices of Kepulauan Seribu in developing tourguide, homestay managers, and the perpetrators of small and medium micro enterprises? (2) how is the obstacles faced by Tourism and Culture offices of Kepulauan Seribu in developing tour guide, homestay managers, and the perpetrators of small and medium micro enterprises? The source of the collected data is gathered for this research is collected from informant, document, documentation and also observation, and using four data analysis namely data collecting, data reduction, data presentation, and conclusion.The result of this research is namely (1) Tourism and Culture offices of Kepulauan Seribu has an active role in giving technical guidance to develop the tour guide, homestay managers, and the perpetrators of small and medium micro enterprises. (2) the obstacles faced by the Tourism and Culture offices of Kepulauan Seribu is the target asked by Tourism and Culture offices of Kepulauan Seribu is not sufficient, the lack of understanding the material conveyed by Tourism and Culture offices of Kepulauan Seribu. Keywords: Tourism and Culture offices of Thousand Island, tour guide, homestay, small and medium micro enterprises. АBSTRАK Jenis penelitian ini menggunakan exploratory research dengan rumusan masalah, yaitu (1) Bagaimana peran aktif dari Suku Dinas Pariwisata dan Kebudayaan Kepulauan Seribu dalam mengembangan tour guide, pengelola homestay, dan para pelaku Usaha Mikro Kecil dan Menengah?. (2) Bagaimana hambatan-hambatan yang dihadapi oleh Suku Dinas Pariwisata dan Kebudayaan Kepulauan Seribu dalam mengembangkan tour guide, pengelola homestay, dan para pelaku Usaha Mikro Kecil dan Menengah? Sumber data yang dikumpulkan dalam penelitian ini diperoleh dari informan, dokumen, dokumentasi dan juga observasi, serta menggunakan empat analisis data yaitu pengumpulan data, reduksi data, penyajian data dan penarikan kesimpulan.Hasil dari penelitian ini yaitu (1) Suku Dinas Pariwisata dan Kebudayaan Kepualaun Seribu berperan aktif dengan memberikan bimbingan teknis untuk mengembangakan tour guide, pengelola homestay, dan pelaku Usaha Mikro Kecil dan Menengah. (2) Hambatan-hambatan yang dihadapi oleh Suku Dinas Pariwisata dan Kebudayaan Kepulauan Seribu yaitu target yang diminta oleh Suku Dinas Pariwisata dan Kebudayaan belum sesuai, kurangnya pemahamanmateri yang disampaikan oleh Suku Dinas Pariwisata dan Kebudayaan Kepulauan Seribu.materi yang disampaikan oleh Suku Dinas Pariwisata dan Kebudayaan Kepulauan Seribu. Kаtа Kunci: Suku Dinas Pariwisata dan Kebudayaan Kepulauan Seribu, tour guide, homestay, Usaha Mikro Kecil dan Menengah.